2020
DOI: 10.2147/jpr.s236336
|View full text |Cite
|
Sign up to set email alerts
|

<p>Analgesic Effect of Morphine Added to Bupivacaine in Serratus Anterior Plane Block Following Modified Radical Mastectomy. Only a Local Effect? Randomized Clinical Trial</p>

Abstract: Background: Serratus anterior plane (SAP) block, a novel regional anesthetic procedure, involves the anterolateral chest wall. Opioid receptors have been found on peripheral nerve terminals, so morphine may have a local action. Objective: This work aimed at exploring the analgesic efficacy of morphine added to bupivacaine in SAPB in patients for whom modified radical mastectomy was conducted and whether it is a mere local effect. Methods: Forty female patients were planned to have modified radical mastectomy p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…SAPB inhibits lateral and anterior cutaneous branches that come from the second to sixth intercostal nerves [ 21 ]. Southgate found that SAPB is recommended for conditions requiring pain management, including thoracotomy, breast surgery, and postmastectomy pain syndrome [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SAPB inhibits lateral and anterior cutaneous branches that come from the second to sixth intercostal nerves [ 21 ]. Southgate found that SAPB is recommended for conditions requiring pain management, including thoracotomy, breast surgery, and postmastectomy pain syndrome [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Figure 2a and 2b illustrates the risk of bias evaluation for the selected studies. Random allocation was applied in almost all included trials [ 10 , 12 , 19 , 21 , 22 ], except in one trial [ 9 ]. Bias from intended interventions was low due to the awareness of participants and people delivering the intervention.…”
Section: R Esultsmentioning
confidence: 99%
“…Nalbuphine is an opioid agent with μ antagonist and κ agonist properties. Studies have shown that opioids as an adjuvant improved the analgesic effects of local anesthetics [ 29 , 30 ]. In this study, we found that UGFICB with ropivacaine plus nalbuphine prolonged the analgesia duration at rest and on passive movement, which is consistent with previous reports [ 15 ].…”
Section: Discussionmentioning
confidence: 99%